Combined method limiting shrinkage–swelling behaviours of expansive soils in Huai'an, China. Issue 5 (30th April 2019) - Miao, Linchang; Wang, Fei; Ye, Wei-min; Jiang, Mingjing; Li, Jie; Shi, Shuibin
Abstract : Controlling the swelling and shrinkage deformation of expansive soil is essential for the design of earth structures surrounded by expansive soils. Swelling and shrinkage deformation could induce severe damages (i.e. cracks and/or distortion) to infrastructures – for example, embankments, pavements and pipelines. In this study, a series of laboratory tests and a field trial on expansive soils in Huai'an, China were conducted to investigate their shrinkage–swelling cycle characteristics. A technology combining quicklime stabilisation and surcharge pressure was proposed to limit the shrinkage–swelling deformation of Huai'an expansive soil in a highway embankment project. The experimental and field test results show that ( a ) the swelling potential of Huai'an expansive soil increased with an increase in the number of drying–wetting cycles without surcharge pressure; ( b ) the swelling potential decreased with an increase in the magnitude of surcharge pressure; ( c ) the addition of quicklime to Huai'an expansive soil combined with surcharge pressure could reduce the swelling potential significantly; and ( d ) the shear strength of expansive soil samples decreased as the number of drying–wetting cycles increased. The measured settlement from the field test indicated that the proposed technique can reduce the swelling potential and control the heaving of Huai'an expansive soil effectively.